Streptococcus Agalactiae Pyomyositis in Diabetes Mellitus. Issue 3 (1st July 2016) - Panikkath, Deepa; Tantrachoti, Pakpoom; Panikkath, Ragesh; Nugent, Kenneth
Abstract : Pyomyositis is an acute infectious disorder affecting the skeletal muscle. Although seen more commonly in the tropics, cases are being reported in temperate countries, including the United States. We report a case of nontropical pyomyositis in a 58-year-old diabetic man who presented with a vague chest wall swelling. His initial clinical presentation and imaging findings suggested an intramuscular hematoma. He later developed fever with increased swelling, and pyomyositis was diagnosed after an aspiration of the swelling yielded Streptococcus agalactiae . Aspiration of the abscess and the use of appropriate antibiotics led to complete resolution of the disease. We discuss possible factors in diabetics that might predispose them to pyomyositis.